Developing Augmented Reality Media On Ecosystems In Science Learning For Grade Vii Students - Indri Yani; Lufty Hari Susanto; Neng Dila Siti Fadilah; Alifia Siti Nurjanah; Dwi Sri Wahyuni; Radika Lesmana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
The development of technology-based learning media has become an essential strategy for improving the quality of science education at the junior secondary school level, particularly in ecosystem topics that require students to understand the interrelationships among ecosystem components comprehensively. In classroom practice, students often encounter difficulties in understanding these concepts because the material is abstract in nature, while instruction is still predominantly conducted through lecture-based methods and textbook-centered learning. This study aimed to develop a Web Augmented Reality (AR)-based learning medium for ecosystem topics that is valid, practical, and effective for use in seventh-grade science learning. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation phases. Data were collected through observations, interviews, expert validation, student response questionnaires, and pretest-posttest assessments. The results indicated that the developed learning media were categorized as valid based on evaluations conducted by both material and media experts. Student responses to the media reached a percentage of 78.06%, indicating that the media were considered practical and appropriate for classroom use. The effectiveness of the media was demonstrated by an increase in students’ mean scores from 2.40 on the pretest to 4.25 on the posttest, with an N-gain score of 0.71 (71%), which falls into the high category. Furthermore, the Paired Sample t-Test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between students’ learning outcomes before and after the implementation of the media. Therefore, the Web Augmented Reality-based learning media on ecosystem topics can be considered valid, practical, and effective in supporting science learning for seventh-grade students.